FLOTATION KINETICS OF MAGNESIUM HYDROXIDE SEDIMENTED FROM SEA WATER - Maksimović, M.; Vukić, Lj.; Vojinović, Đ.; Mandić, J. (Journal of Engineering & Processing Management, 2009)
Synthetic sea water has been taken as a referential sample, in which Mg(OH)2 had been sedimented, in order to reduce biological effects and confirm reproducibility of results of the familiar composition sample. The synthetic sea water was prepared according to the scientifically developed procedure. Flotation experiments were performed in the apparatus for flotation under pressure and recoveries of floated Mg(OH)2 were determined depending on the time of flotation. The results obtained on the referential sample of the synthetic water were also tested on the sample of natural sea water and presented comparatively during work. Flotation kinetics is in most cases described by an equation of the first or second degree. However, it was established that flotation kinetics of Mg(OH)2 as chemical sediment with both types of prepared magnesium hydroxide suspension, sedimented in both the synthetic and natural sea water corresponded to the velocity of reaction n = 1.5 degree, which fully corresponds to Horst Morris’s theoretical postulates in the theory of flotation kinetics.